IP Network-based Multi-agent Systems for Industrial Automation Information Management, Condition Monitoring and Control of Power Systems - Buse, D. P.; Wu, Q. H.; SpringerLink (Online service) (London : Springer London, 2007)
A mobile agent is a software program with the capability to suspend its execution and resume it on another computer. Agents are a relatively recent development in computer science, which have become a popular and useful methodology for the modelling and implementation of distributed systems, particularly those consisting of a number of largely autonomous components. The extensive use of multi-agent systems in various areas including information management, industrial control and manufacturing systems, suggests that the multi-agent systems methodology may also be appropriate for the design of power system automation systems. IP Network-based Multi-agent Systems for Industrial Automation is the first book to present an introduction to the use of the Internet protocol suite and multi-agent systems for the information management, online monitoring and control of distributed power system substations. An open architecture is proposed, in which mobile agents are applied to the retrieval and analysis of substation data, and to remote operator intervention. A prototype implementation of this architecture is also described, which has been demonstrated and evaluated using a substation simulator. IP Network-based Multi-agent Systems for Industrial Automation is an excellent reference for postgraduates, researchers and academics in engineering and computer science, as well as engineers in system automation and managers in distributed industrial systems.
Agents, Multi-agent Systems and Mobile Code -- An Agent-based Architecture for Power System Automation -- Static Components of Architecture -- Applications of Mobile Agents -- Multi-agent-based Substation Information Management System -- Evaluation and Analysis.
Keywords: Engineering; Control engineering; Robotics; Mechatronics; Power electronics; Engineering; Control, Robotics, Mechatronics; Information Systems Applications (incl. Internet).; Power Electronics, Electrical Machines and Networks; Electronic books